THE NEXUS BETWEEN FINANCIAL DEVELOPMENT, INSTITUTIONS AND ECONOMIC GROWTH: EVIDENCE FROM HIGH-, MIDDLE- AND LOW-INCOME COUNTRIES - Babar Hussain; Kifayat Ullah; Sajjad Haider; Muhammad Usman; Sarah Anwar; Touqeer Ahmad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This study highlights the impact of financial development on economic growth by exploring the role of different institutions. Regarding this context, we utilized balanced panel dataset of 57countries categorized into (high-income, middle-income and low-income) from 1980-2017 and analyzed it by using 2 step system GMM. The overall results showed that there is a conclusive impact of financial development on economic growth of the countries. Findings showed that financial development is more strongly playing its role in middle income countries as compared to high-income countries where more finance negatively affects the growth and in low-income countries the impact of financial sector development is weakest. But under the presence of sound institutions which are political stability, government effectiveness, corruption and law and order the impact of financial development in high-income economies as well as in middle-income countries is positive as well as significant except in the low-income countries so, increase in finance in the absence of strong institutions may not successfully contributing towards economic benefits.